PENGARUH AUDITOR-CLIENT SOCIAL MISMATCH DAN TIPE SUPERVISOR TERHADAP KUALITAS AUDIT - Cahyonowati, Nur; ,, Darsono (KINERJA, 2015)
This research aims to provide empirical evidence of the behavior of audit staff that reflects the quality ofaudit performed. This research predicts that audit quality is determined by social mismatch between auditor staffand client. This research also examines the effect of supervisor type on audit quality according to McGregor’stheory. This research is carried out using 2x2 between subject experimental designs. The subjects are studentsin Accounting Department of state university in Central Java.The result indicates that social mismatch between auditor staff and client is able to decrease probabilityto collect audit evidence. However, type of supervisor is not found to be significant determinant of probabilityto collect audit evidence. This research implies the need to intensify training in accounting firm to overcomemismatch between auditor staff and client.Keywords: social mismatch, type of supervisor, audit quality, experiment